Baseline Summary Report 1st Annual Panel Survey 2021: Comprehensive Evaluation of the Community Health and Nutrition (CHN) program. - Jordan Nutrition Innovation Lab. (Tufts University. Tisch Library., 2023)
A baseline (Panel 1) survey, part of a prospective cross-sectional evaluation, was conducted between September-November 2021, to capture data and information in establishing the prevailing situation in the three CHN-targeted governorates of Amman, Karak, and Zarqa on maternal, infant, and young child nutrition, and the status of pregnant and lactating women (PLW) and service providers (SP) Two separate quantitative surveys were implemented. The first one was a PLW survey administered to 1079 pregnant and lactating women with child under the age of 2 years in 24 health facilities selected and targeted by the CHN program. The second, was a SP survey administered to 70 service providers (health care providers) working in the maternal and child health department at the CHN targeted health facilities across the three governorates of Jordan (Amman, Karak, and Zarqa); Keywords: nutrition, infant and young child feeding practices, maternal nutrition status, pregnant and lactating women, exclusive breastfeeding.; Tufts University Friedman School of Nutrition Science and Policy Cooperative Agreement Associate Award No.: 72027820LA00003.